2020
DOI: 10.1136/postgradmedj-2020-137773
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound augments physical examination learning by undergraduate medical students

Abstract: BackgroundLittle is known about the impact of the provision of handheld point-of-care ultrasound (POCUS) devices on physical examination skills of medical students.MethodsWe describe an educational initiative that comprised a POCUS workshop followed by allocation of a POCUS device to medical students for use over the subsequent 8 weeks. They were encouraged to scan patients and correlate their physical examination findings. A mobile instant messaging group discussion platform was set to provide feedback from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Again, overcrowding is the main problem in low- to middle-income countries. As the pressures continue to mount, the solution may simply be the availability of handheld ultrasound devices, which are small, affordable, feasible, and easy to access, which is consistent with other studies [ 38 , 39 , 40 , 41 , 42 , 43 ]. Finally, the majority of learners reported that they felt the time to study in this rotation was too short.…”
Section: Discussionsupporting
confidence: 78%
“…Again, overcrowding is the main problem in low- to middle-income countries. As the pressures continue to mount, the solution may simply be the availability of handheld ultrasound devices, which are small, affordable, feasible, and easy to access, which is consistent with other studies [ 38 , 39 , 40 , 41 , 42 , 43 ]. Finally, the majority of learners reported that they felt the time to study in this rotation was too short.…”
Section: Discussionsupporting
confidence: 78%
“…Some evidence suggests that physicians are less inclined to utilize physical examination skills and that the quality and proficiency of these skills is lacking and prone to error [ 40 , 41 ]. POCUS is proven, to improve bedside physical exams by medical students and residents to the point that one author recommends “insonation” as a component of the physical exam [ 4 , 40 , 42 ]. Recent studies demonstrate that incorporating HHU devices into undergraduate medical education was well received by students, improved conceptual understanding of anatomy, and improved student confidence and diagnostic accuracy when performing physical examinations [ 42 44 , 45 ••, 46 ].…”
Section: Current Use Of Hhus In the Edmentioning
confidence: 99%
“…Trainees view POCUS education as valuable and provides them with more confidence in their diagnostic capabilities and ultrasound skills [12,15,16]. POCUS education is associated with improved student attitude, confidence, and ability to perform physical exams and improved evaluation of these exam skills in Objective Standardized Clinical Examination (OSCE) scores [17][18][19][20]. POCUS education has also been associated with increased student confidence in performance of bedside procedures [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%